National, regional, and global sex ratios of infant, child, and under-5 mortality and identification of countries with outlying ratios: a systematic assessment - Dr. Leontine Alkema, PhD; Fengqing Chao, BSc; Danzhen You, PhD; Jon Pedersen, MA; Cheryl C Sawyer, MA (Elsevier, 2014)
Background: Under natural circumstances, the sex ratio of male to female mortality up to the age of 5 years is greater than one but sex discrimination can change sex ratios. The estimation of mortality by sex and identification of countries with outlying levels is challenging because of issues with data availability and quality, and because sex ratios might vary naturally based on differences in mortality levels and associated cause of death distributions. Methods: For this systematic analysis, we estimated country-specific mortality sex ratios for infants, children aged 1-4 years, and children under the age of 5 years (under 5s) for all countries from 1990 (or the earliest year of data collection) to 2012 using a Bayesian hierarchical time series model, accounting for various data quality issues and assessing the uncertainty in sex ratios. We simultaneously estimated the global relation between sex ratios and mortality levels and constructed estimates of expected and excess female mortality rates to identify countries with outlying sex ratios. Findings: Global sex ratios in 2012 were 1·13 (90% uncertainty interval 1·12-1·15) for infants, 0·95 (0·93-0·97) for children aged 1-5 years, and 1·08 (1·07-1·09) for under 5s, an increase since 1990 of 0·01 (−0·01 to 0·02) for infants, 0·04 (0·02 to 0·06) for children aged 1-4 years, and 0·02 (0·01 to 0·04) for under 5s. Levels and trends varied across regions and countries. Sex ratios were lowest in southern Asia for 1990 and 2012 for all age groups. Highest sex ratios were seen in developed regions and the Caucasus and central Asia region. Decreasing mortality was associated with increasing sex ratios, except at very low infant mortality, where sex ratios decreased with total mortality. For 2012, we identified 15 countries with outlying under-5 sex ratios, of which ten countries had female mortality higher than expected (Afghanistan, Bahrain, Bangladesh, China, Egypt, India, Iran, Jordan, Nepal, and Pakistan). Although excess female mortality has decreased since 1990 for the vast majority of countries with outlying sex ratios, the ratios of estimated to expected female mortality did not change substantially for most countries, and worsened for India. Interpretation: Important differences exist between boys and girls with respect to survival up to the age of 5 years. Survival chances tend to improve more rapidly for girls compared with boys as total mortality decreases, with a reversal of this trend at very low infant mortality. For many countries, sex ratios follow this pattern but important exceptions exist. An explanation needs to be sought for selected countries with outlying sex ratios and action should be undertaken if sex discrimination is present. Funding: The National University of Singapore and the United Nations Children's Fund (UNICEF).